2010
DOI: 10.1038/npp.2010.85
|View full text |Cite
|
Sign up to set email alerts
|

CpG Methylation in Neurons: Message, Memory, or Mask?

Abstract: The study of CpG methylation of genomic DNA in neurons has emerged from the shadow of cancer biology into a fundamental investigation of neuronal physiology. This advance began with the discovery that catalytic and receptor proteins related to the insertion and recognition of this chemical mark are robustly expressed in neurons. At the smallest scale of analysis is the methylation of a single cytosine base within a regulatory cognate sequence. This singular alteration in a nucleotide can profoundly modify tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 105 publications
(149 reference statements)
0
26
0
1
Order By: Relevance
“…It is possible that this is important as prior studies indicate that the methylation status of even a single CpG can determine whether a gene is transcribed (Sharma et al, 2010).…”
Section: Gadd45b and Psychosis Dp Gavin Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that this is important as prior studies indicate that the methylation status of even a single CpG can determine whether a gene is transcribed (Sharma et al, 2010).…”
Section: Gadd45b and Psychosis Dp Gavin Et Almentioning
confidence: 99%
“…Further, the relationship between CpG methylation and transcription is not linear with transcription beginning at times before it is demethylated (Buschhausen et al, 1985;Sharma et al, 2010). Finally, recent studies indicate that 5HMC accounts for 14% of the methylcytosines in the brain Munzel et al, 2010).…”
Section: Gadd45b and Psychosis Dp Gavin Et Almentioning
confidence: 99%
“…DNA methylation has been reported to play a role in development [2], gene silencing [3], and carcinogenesis [4]. In addition, the CpG dinucleotide, which represents the main target for methylation in humans, is a known hot spot for pathological mutations [5], [6].…”
Section: Introductionmentioning
confidence: 99%
“…9,17,18 The precise mechanisms by which neuronal DNA may be demethylated is unclear, 18 but it has been suggested that growth arrest and DNA damageinducible protein 45β (GADD45β) may facilitate DNA demethylation and thereby influence memory. 19 Indeed, hippocampal GADD45β expression is increased when animals are exposed to a novel environment and permitted to explore (i.e., new contextual learning).…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%